Adaptation of Afro Colombian students to an intercultural context in universities in Bogotá (2016)
From color of skin and ways of speaking to interculturality backgrounds, minorities as Colombian afro descendants are still suffering because of discriminatory issues, especially in universities in Bogotá, where higher education is addressed towards globalization. These types of violations affect the development of Colombian afros in the education arena, they sometimes experience isolation and episodes of discrimination in the study hall, promoting social inequity and injustice. In this context, afro descendants need to include the adaptation to the social requirements present in the capital city in order to achieve individual projects. Nevertheless, society manifest acts of discrimination in the lecture room, and in different spheres of human relations and interactions affecting the processes for proper advance in the generation of elements for successful communication. Yet, afro students adapt to academic atmospheres by integrating and assuming roles proper of that environment.